Strategy Analysis to Improve Consultant Qualification in Surabaya - Faris Afif Octavio; I Putu Artama Wiguna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), ITS, 2019)
Electronic Procurement Agency indicated that in the 2015 up to 2017 project for infrastructure consulting services with qualifying middle to upper class in the Minister for Republic Works and Human Sattlements increased 5% per year. The Development Institution Construction Services shows that number of consulting firm in Surabaya city with qualifying middle to upper level less than 20 company, while the company consultant were at the middle to lower is very much. This research aimed to producing strategy in the qualification a consulting firm in Surabaya city. The variables used in a study are internal and external factors in increasing the consultant qualification. This variables analysis using Strength Weakness Opportunity Treats Matrix (SWOT), External Internal Matrix (I-E), and Quantities Strategic Planning Matrix (QSPM) used to determine the best strategy. The result of the study indicate several strategies that can be used to improve consultans qualification. The first strategy is joint venture with other consulting firm to enhance experiences and increase the income of company. The second strategy is improve the quality of human resources and adjust infrastructure facilities with international quality standard namely ISO 9001. The third strategy is work on projects that have high risk.